Implications of Keeping-Up-with-the-Joneses Behavior for the Equilibrium Cross Section of Stock Returns: International Evidence - GÓMEZ, JUAN-PEDRO; PRIESTLEY, RICHARD; ZAPATERO, FERNANDO (Journal of Finance, 2009)
This paper tests the cross-sectional implications of “keeping-up-with-the-Joneses” (KUJ) preferences in an international setting. When agents have KUJ preferences, in the presence of undiversifiable nonfinancial wealth, both world and domestic risk (the idiosyncratic component of domestic wealth) are priced, and the equilibrium price of risk of the domestic factor is negative. We use labor income as a proxy for domestic wealth and find empirical support for these predictions. In terms of explaining the cross-section of stock returns and the size of the pricing errors, the model performs better than alternative international asset pricing models.